Poems to learn by heart - Kennedy, Caroline, 1957-; Muth, Jon J. (New York : Disney Hyperion Books, 2013)
For this companion to her "New York Times"-bestselling collection "A Family of Poems," Kennedy has hand-selected more than 100 of her favorite poems that lend themselves to memorization.
Includes indexes.
NP
Keywords: American poetry -- Juvenile literature; English poetry -- Juvenile literature; Children's poetry